Olive oil characterization of cv Arauco harvested at different times in areas with early frost in Mendoza, Argentina - Trentacoste, Eduardo Rafael (2019)
BACKGROUND: Arauco is the only olive cultivar autochthonous from Argentina, and little has been reported so far regarding the management of this crop. In this work, variations in fruit and chemical characteristics of olives harvested in a wide range of dates and seasons are reported for this cultivar in two sites of Mendoza province in Central West Argentina. RESULTS: During the harvest periods evaluated, fruit oil content on dry basis remained maximum and stable, but fruit oil content on fresh basis increased as water content decreased with the delay in harvest. Harvest date modified the maturity index of fruits as well as the oxidative stability and phenolic content of oil. In contrast, the fatty acid profile was not consistently affected by harvest date. Environmental conditions, mainly the occurrence and intensity of frosts, closely influenced oil quality as well as maturity advancement with the delay in harvest. CONCLUSION: Olives with a maturity index lower than two harvested before mid‐May was the most appropriate harvest time in order to obtain Arauco oil with high oil yield and good chemical quality. Fruits harvested after mid‐May were exposed to minimum temperatures between ‐1.2 °C and ‐4.0 °C, producing oil with low phenolic compounds and oxidative stability.